Bioefficacy of Pesticides Against Pod Borer Lampides boeticus L. (Lycaenidae: Lepidoptera) in Summer Mung Bean - Verma, S K (Annals of Arid Zone, 2016)
Two concentrations each of endosulfan 35EC, monocrotophos 36SC and carbaryl 50WP were evaluated against pod borer Lampides boeticus in the summer crop of mung bean cv. Pusa Baisakhi. The insecticides were applied 20 days after sowing @ 500 L ha-I . Monocrotophos 0.04% spray afforded the best protection up to 25 days after spray, with only 4.7 to 8.7% pods damaged by the pod borer. It was followed by monocrotophos 0.02%, endosulfan 0.07% and carbaryl '0.2%. which were statistically at par. The bioefficacy of insecticides, in decreasing order, was inferred as monocrotophos 0.04%>monocrotophos 0.02% = endosulfan 0.07%>carbaryl 0.2o/O>endosulfan 0.035%>carbaryl 0.1%.